2016
DOI: 10.5888/pcd13.160092
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and Health-Related Quality of Life Among US Adults With Arthritis, Medical Expenditure Panel Survey, 2010–2012

Abstract: IntroductionOur objective was to determine the relationship between polypharmacy (treatment with prescription drugs from 6 or more drug classes concurrently) and health-related quality of life (HRQoL) among US adults with arthritis.MethodsWe conducted a retrospective cohort study that used 2-year longitudinal data from the Medical Expenditure Panel Survey to analyze a cohort of 6,132 adults aged over 21 years with arthritis. Measures of HRQoL were the summary scores from the mental component summary (MCS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 17 publications
3
34
2
1
Order By: Relevance
“…Consistent with the current study findings, earlier studies have also demonstrated an association between the increased number of prescribed medications and HRQoL . An earlier retrospective cohort study aimed to determine the association between polypharmacy and HRQoL among US adults with arthritis using the mental component summary (MCS) and physical component summary (PCS) scores found that adults with arthritis taking six or more medications concurrently were found to have significantly lower MCS and PCS scores than adults who were prescribed less than six medications . Another cross‐sectional descriptive study used the EQ‐5D to describe the association between medication‐related factors and HRQoL in patients older than 65 years found that patients who were using more than ten medicines were found to have poor HRQoL .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the current study findings, earlier studies have also demonstrated an association between the increased number of prescribed medications and HRQoL . An earlier retrospective cohort study aimed to determine the association between polypharmacy and HRQoL among US adults with arthritis using the mental component summary (MCS) and physical component summary (PCS) scores found that adults with arthritis taking six or more medications concurrently were found to have significantly lower MCS and PCS scores than adults who were prescribed less than six medications . Another cross‐sectional descriptive study used the EQ‐5D to describe the association between medication‐related factors and HRQoL in patients older than 65 years found that patients who were using more than ten medicines were found to have poor HRQoL .…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] An earlier retrospective cohort study aimed to determine the association between polypharmacy and HRQoL among US adults with arthritis using the mental component summary (MCS) and physical component summary (PCS) scores found that adults with arthritis taking six or more medications concurrently were found to have significantly lower MCS and PCS scores than adults who were prescribed less than six medications. [25] Another cross-sectional descriptive study used the EQ-5D to describe the association between medication-related factors and HRQoL in patients older than 65 years found that patients who were using more than ten medicines were found to have poor HRQoL. [26] The increased number of prescribed medications may lead to an increased risk of inappropriate medication use, under-use of effective treatments, medication errors, poor adherence, drug-drug and drug-disease interactions and most importantly increase the potential of medication side effects which could have a negative impact on HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple faces for polypharmacy also involve considering the type of data or medical element used as basis for its definition. The literature involves some studies that used the actual number of drugs [1,2,4,7,17], and others that used the number of drug classes [18,19,20]. This makes a substantial difference for polypharmacy results.…”
Section: Chapter 2: Background and Related Work 21 Problem Of Polyphmentioning
confidence: 99%
“…Others used: 2 or more drugs, 3 or more, 5 or more, 6 or more, 10 or more, but the most common number used to define polypharmacy was 5. As reported in the literature, some studies used the actual drugs [1,2,4,7,17], while others used drug classes [18,19,20,21].…”
Section: Definitions Of Polypharmacymentioning
confidence: 99%
See 1 more Smart Citation